UNVEILING SHADOWS: A COMPREHENSIVE EXAMINATION OF VIOLENCE AGAINST WOMEN IN INDIA AND METHODOLOGICAL CHALLENGES IN RESEARCH - Shabir Ahmad Lone; Irshad Ahmad Reshi; Shamweel Iqbal Dar; Nadeem Akhtar4; Mohammad Ishaq Lone (PT. Radja Intercontinental Publishing, 2025)
This research article delves into the persistent challenge of violence against women in India, examining its various forms and societal implications. It scrutinizes the ambiguity in defining such violence and the subsequent methodological challenges in research, particularly addressing the sensitive nature of the subject. The study highlights the complex interplay of factors contributing to increased reports of sexual violence against women, including patriarchy, education, and disparities in gendered power dynamics. Despite societal changes, the normalization of violence complicates the assessment of actual increases. The paper underscores the multifaceted nature of the issue, influenced by contextual factors, intermediate factors, and societal effects. The research proposes that attempts have been made to eliminate domestic violence, yet some programs demonstrate less success. The analysis emphasizes the interconnectedness of sexual harassment with broader economic, political, and cultural contexts. Despite women's increased confidence, the reluctance to report violence persists, attributed to the normalization of such incidents. The conclusion advocates for improved legislation to address the pervasive issue effectively. The research encounters challenges in defining violence and underlines the need for enhanced research efforts to better understand gender violence and design effective interventions.